News media commercialization in Chindia: Changing theoretical perceptions. (December 2020) - Mammadov, Rashad
There are many descriptions of media realities in China and India. Few of them, however, look at these countries from the theoretical classification framework, and those who do often do not pay proper attention to the Western orientation of existing classifications. Denis McQuail's models of dominance and pluralism are not frequently mentioned in global media studies, and this article adds to the scholarly discussion about their use to explain media environments in the countries like India, which uses Western standards of media system, although having a cultural and historical background that is different from the West, and China, which despite implementation of one part of the Western approach, such as commercialization, ignores or rejects the others.